DAMPAK PERUBAHAN IKLIM TERHADAP USAHATANI PADI DI DESA WANGUK KECAMATAN ANJATAN KABUPATEN INDRAMAYU - Getmi Nuraisah; Rani Andriani Budi Kusumo (Universitas Galuh Ciamis, 2019)
One of the biggest threats in the world of agriculture is the occurrence of global climate change which is likely to result in crop failure. Agriculture and climate change have a very close connection, because agricultural sector is very dependent and very vulnerable to climate change, so that the knowledge of farmers in the magnitude of climate change is needed. This study aims to examine the extent to which farmers' knowledge of climate change is happening and the impacts caused by climate change, especially on rice. This research was carried out using qualitative design with